Hydrodynamic Characteristics of Offshore Wind Turbine Pile Foundations Under Combined Focusing Wave-Current Conditions - Renwei Ji; Xiangquan Li; Yonglin Ye; Renqing Zhu; Ke Sun; Miankui Wu; Fei Huang; Ratthakrit Reabroy (Journal of Marine Science and Engineering)
In extreme marine environments, the interaction between offshore wind turbine pile foundations (OWTPFs) is critical, and the associated hydrodynamic loads are complex. This study focused on fixed OWTPFs and used computational fluid dynamics (CFD) to numerically simulate the flow field around pile foundations under the combined action of focusing waves and current. The objective was to investigate the influence of different focusing wave and current parameters on the hydrodynamic properties of the pile foundations. The findings indicate the following: (1) When the wave and current directions are opposite, the maximum wave force on the pile foundations is greater than when they are aligned. (2) Large-amplitude focusing waves around pile foundations generate secondary loads, which are nonlinear and lead to a rapid increase in the wave force. These secondary loads are short-lived and particularly prominent near the front row of pile foundations. (3) The influence of the group pile effect diminishes under high-amplitude waves, where the wave component dominates the generation of the dimensionless wave force, and the impact of the current on this force decreases.